105 The Nutrition of Glutamate, Glutamine, Glycine, Proline and Arginine in Ruminants. (7th December 2018) - Brake, D
Abstract: Ruminants have a complex gastrointestinal tract that allows microbial fermentation of feed prior to nutrient absorption. Ruminal microorganisms are apparently responsive to nutrients from feed and to nutrients cycled from non-alimentary tissues. Subsequently, physiological responses among postruminal tissues to changes in nutrient flows resulting from changes in ruminal fermentation may have large influence on the digestion and use of nearly all nutrients consumed by ruminants. Classically, glutamate, glutamine, glycine, proline and arginine have been considered as nutritionally nonessential amino amino acids; however, these amino acids contribute to a myriad of physiological functions necessary to support life, and it is possible that the role of these amino acids in nutrient cycling and intra- and extra-cellular single transduction may have even greater impact on regulation of nutrient utilization in ruminants in comparison to nonruminants. Indeed, an increasing amount of data indicates that metabolism of glutamate, glutamine, glycine, proline and arginine may be integral to optimal digestion and absorption of nutrients from different segments of the ruminant gastrointestinal tract when nutrient flows from feed do not allow optimal digestion. Additionally, some of these amino acids and their metabolites may also allow for greater splanchnic release of nutrients to peripheral tissues, and can ameliorate limitations in amino acid biosynthesis to allow greater protein synthesis from targeted tissues. Even though more information is needed before the impacts of glutamate, glutamine, glycine, proline and arginine on regulation of nutrient use in ruminants can be completely elucidated, it is clear that an understanding of the flows of both nutritionally essential and non-essential amino acids will likely be required to develop nutritional strategies that allow optimal performance and nutrient utilization in ruminants.